Government Rocade - A Genuine Constitutional Solution or an Illusory, Discretionary One? - Oana ŞARAMET (Modern Visions of Public Law Editură:ADJURIS, 2023)
Democracy is also about majority, a majority that is increasingly difficult to achieve as a result of holding an election to appoint representatives to Parliament. However, the governance of a state must be ensured, which is why the constituent legislator has the difficult task of finding constitutional solutions to build such a majority. However, such majorities will always be fragile, and those who form them will try to find the most surprising solutions to ensure their survival. One such solution could be the governmental rocade envisaged by the current parliamentary majority in Romania? Can the constitutional rules on the formation of a government be interpreted and applied in a discretionary manner? Through this study we aim to identify possible constitutional solutions for such a governmental rotation, their viability, including by analysing the jurisprudence of the Constitutional Court, but also the constitutional rules concerning the formation of government in countries with a political regime similar to ours, such as Portugal, Finland, as well as the limits of a possible discretionary power in the implementation of such a rotation.
Keywords: government formation; government rotation; parliamentary majority; constitutionality; discretionary power.